2008
DOI: 10.1093/jac/dkn088
|View full text |Cite
|
Sign up to set email alerts
|

Novel structural analogues of piperine as inhibitors of the NorA efflux pump of Staphylococcus aureus

Abstract: A newly identified class of compounds derived from a natural amide, piperine, is more potent than the parent molecule in potentiating the activity of ciprofloxacin through the inhibition of the NorA efflux pump. These molecules may prove useful in augmenting the antibacterial activities of fluoroquinolones in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(80 citation statements)
references
References 31 publications
0
74
0
1
Order By: Relevance
“…Ampicillin and cefadroxil were chosen as representatives for penicillins and cephalosporins in these assays (see Methods andKumar et al, 2008 andMacLeod et al, 2009 for details). The general patterns observed in the experiments above were duplicated in these assays.…”
Section: Analysis Of Killing Kinetics Indicate That Pbp5 Pbp6 and Damentioning
confidence: 99%
“…Ampicillin and cefadroxil were chosen as representatives for penicillins and cephalosporins in these assays (see Methods andKumar et al, 2008 andMacLeod et al, 2009 for details). The general patterns observed in the experiments above were duplicated in these assays.…”
Section: Analysis Of Killing Kinetics Indicate That Pbp5 Pbp6 and Damentioning
confidence: 99%
“…Several compounds, such as reserpine, behave as if they inhibit efflux pumps and hence have become known as efflux pump inhibitors (EPIs) [4]. Since that time, numerous phytochemicals have been shown to have activity against S. aureus or other Grampositive bacteria, or to act as potential EPIs with antimicrobials for Gram-positive bacteria [5][6][7][8][9][10][11]. Unfortunately, most of the plant-derived compounds have little or no activity with antibiotics against Gram-negative bacteria and it was suggested that, as many plant pathogens are Gram-negative bacteria, plants may not produce molecules effective against these organisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports in the literature where natural products have demonstrated enhancement of antimicrobial activity (Khan et al, 2006;Stavri et al, 2007;Werle, 2008;Kumar et al, 2008;Lechner et al, 2008;Sharma et al, 2010). However, the number of natural compounds behaving synergistically with antifungals is minimal.…”
Section: Introductionmentioning
confidence: 99%